Proceedings of the 14th International Conference on Interaction Design and Children 2015
DOI: 10.1145/2771839.2771900
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting children's tablet-based reading experiences with variable friction haptic feedback

Abstract: This paper explores the integration of tactile feedback into children's electronic books (e-books) through variable friction surface haptics enabled by the TPaD Tablet technology. Through a user study with 10 pairs of children and their parents, we examine how children and parents conceive of and add haptics to a popular e-book. We report conceptual and practical differences in the ways in which children of various ages (3-8 years old) and adults envision haptic feedback within an e-book and conclude with a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…It is of note that while attitudes were neutral, on average, parents had more negative attitudes toward haptic technology than technology more generally. We argue that these findings fit research fromCingel et al (2015) in which parents were somewhat skeptical of adding haptics to the e-book reading experience. In that study, most participants reported that they could see the value of haptic feedback to enhance reading e-books, but also noted that the digital haptic addition could not replace the very real feeling of textures in print books.…”
supporting
confidence: 75%
“…It is of note that while attitudes were neutral, on average, parents had more negative attitudes toward haptic technology than technology more generally. We argue that these findings fit research fromCingel et al (2015) in which parents were somewhat skeptical of adding haptics to the e-book reading experience. In that study, most participants reported that they could see the value of haptic feedback to enhance reading e-books, but also noted that the digital haptic addition could not replace the very real feeling of textures in print books.…”
supporting
confidence: 75%
“…All participants were introduced and given time to explore a Tanvas TPaD tablet. The TPaD tablet (see Cingel et al, 2015 for a review of the technology) uses TanvasTouch technology embedded in a standard Android tablet. This technology allows for programmatically varying the friction between the users' fingertip and the flat glass display surface, creating the sensation of tactile patterns.…”
Section: Haptic Feedback Tabletmentioning
confidence: 99%
“…All participants experienced the stimuli on a Tanvas TPaD tablet. The TPaD tablet (see [62] for a review of the earlier technology) is an Android tablet with the embedded technology of TanvasTouch. Using electrostatics to control friction and create virtual touch, TanvasTouch software allows for programming specific textures and haptics effects to be associated with the swipe of fingers on any touchscreen [63].…”
Section: Haptic Tabletmentioning
confidence: 99%
“…It could be that merely dragging their fingers around on the tablet was not enough of the physical manipulation needed for this type of learning [50,51]. Future research would be wise to consider other STEM concepts better suited to haptic feedback experiences such as learning about fire, space, or animals that are unrealistic or otherwise impossible to touch in real life [62].…”
Section: Game and Haptic Feedbackmentioning
confidence: 99%